Project Governance Implementing Corporate Governance and Business Ethics in Nonprofit Organizations - Renz, Patrick S.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2007)
Do you know where your investments go? How effective and accountable are the resources used in the international development? How can intercultural frictions, governance scandals, or corruption be prevented? Based on a case study the author unveils a gap in the governance of development projects, a gap between implementation and governance, ultimately hindering effective, transparent and accountable usage of resources. Illustrated with entertaining examples the author, himself a senior manager in development and business, develops a Project Governance model. Overcoming shortcomings of the theories of corporate governance and business ethics, of best practices in development and project management, the Project Governance Model is a concrete model for practitioners and academics. Its six modules build an integrated, strategically oriented and ethically reflected platform for a more truthful and efficient cooperation in difficult projects or programs such as in development.
Objectives and approach -- Is there a need for project governance? -- The roles of governance in development projects -- The Project Governance Model -- Conclusions.
Keywords: Business; Entrepreneurship; Management; Organization; Planning; Business ethics; Ethics; Development economics; Business and Management; Business Ethics; Entrepreneurship; Development Economics; Organization; Management; Ethics; Electronic books